Molecular weight of surface immobilized hyaluronic acid influences CD44-mediated binding of gastric cancer cells. Issue 1 (December 2018) - Amorim, Sara; Costa, Diana; Freitas, Daniela; Reis, Celso; Reis, Rui; Pashkuleva, Iva; Pires, Ricardo
Abstract The physiological importance of the interactions between hyaluronic acid (HA) and its main membrane receptor, CD44, in pathological processes, e.g. cancer, is well recognized. However, these interactions are mainly studied in solution, whereas HA in the extracellular matrix (ECM) is partially immobilized via its interactions with other ECM components. We therefore, developed substrates in which HA is presented in an ECM-relevant manner. We immobilized HA with different molecular weights (Mw ) in a Layer-by-Layer (LbL) fashion and studied the interactions of the substrates with CD44 and two human gastric cancer cell lines that overexpress this receptor, namely AGS and MKN45. We demonstrate that MKN45 cells are more sensitive to the LbL substrates as compared with AGS. This difference is due to different CD44 expression: while CD44 is detected mainly in the cytoplasm of AGS, MKN45 express CD44 predominantly at the cell membrane where it is involved in the recognition and binding of HA. The invasiveness of the studied cell lines was also evaluated as a function of HA Mw . Invasive profile characterized by low cell adhesion, high cell motility, high expression of cortactin, formation of invadopodia and cell clusters was observed for MKN45 cells when they are in contact with substrates presenting HA of high Mw .